2022
DOI: 10.1007/s10734-022-00978-7
|View full text |Cite
|
Sign up to set email alerts
|

Foreign early career academics’ well-being profiles at workplaces in Japan: a person-oriented approach

Abstract: The well-being of foreign early career academics (FECAs) has been the subject of research attention in relation to present demanding academic milieux in general and to those unfamiliar workplace settings in particular. A traditional variable-oriented approach that focuses on mean scores can easily gloss over the diverse nature of the group under study. Our study, conducted in Japan, took a person-oriented approach and identified FECAs’ distinct well-being profiles and the associations of their personal attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The study examines the sensemaking of international academics in terms of their decisions to remain at their affiliations despite perceptual unaccommodating host environments and perceptions of being tokenized. While scholarly attention has persistently focused on the typology of international academics in Japan, including their demographics, work roles (Huang, 2018b), integration (Brotherhood et al, 2020), and well-being (Sakurai & Mason, 2022), this study addresses a crucial aspect of internationalization by recognizing the indispensable role of retaining minority academics (Chun & Evans, 2009). Thus, the study proposes a significant framework for advancing institutional internationalization in Japan based on the retention of international academics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study examines the sensemaking of international academics in terms of their decisions to remain at their affiliations despite perceptual unaccommodating host environments and perceptions of being tokenized. While scholarly attention has persistently focused on the typology of international academics in Japan, including their demographics, work roles (Huang, 2018b), integration (Brotherhood et al, 2020), and well-being (Sakurai & Mason, 2022), this study addresses a crucial aspect of internationalization by recognizing the indispensable role of retaining minority academics (Chun & Evans, 2009). Thus, the study proposes a significant framework for advancing institutional internationalization in Japan based on the retention of international academics.…”
Section: Discussionmentioning
confidence: 99%
“…Parrish et al (2022) identified the major factors that influence the satisfaction of English instructors with Japanese universities by conducting a national survey on perceived respect, autonomy, departmental relationship, and work-life balance. Additionally, Sakurai and Mason (2022) characterized international academics under three categories according to their well-being in Japan based on scores for stress and sense of belonging. Surprisingly, only Chen and Chen (2023) specifically addressed the career plans of international academics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…19 The ambiguity of my status was aggravated by the fact that there are no signals on the Tōdai track to tenure. JNUs are often indifferent to the ethno-national make up of scholars, too, with young foreign faculty on fixed term contracts equally bereft of "belonging" (Sakurai & Mason, 2023). Such insecurity is a neoliberal technique of control, with universities the unashamed pioneers of the precarious gig economy.…”
Section: Tōdai and Ethno-national Organisational Culturementioning
confidence: 99%
“…We considered these measures suitable for academic communities (content validity), and studies have indicated the survey's psychometric adequacy in the HEI context (e.g. Pace et al, 2019; Sakurai & Mason, 2022).…”
Section: This Studymentioning
confidence: 99%
“…Have you felt this kind of stress recently?’ (1 = not at all to 9 = very much ) (Elo et al, 2003). Studies have validated this measure in various occupational settings (Elo et al, 2003) including HEIs (Opstrup & Pihl‐Thingvad, 2016; Sakurai & Mason, 2022).…”
Section: This Studymentioning
confidence: 99%